Improving United States HPV vaccination rates: Factors predictive of parental attitudes towards middle school entry requirements - Jill Desch; Erika Thompson; Jason Beckstead; Heather Owens; Morgan Richardson Cayama; Paula Hernandez; Jacqueline Valencia; Gregory Zimet; Cheryl Vamos; Ellen Daley (Taylor & Francis Group, 2024)
Although the human papillomavirus (HPV) vaccine is effective at preventing infection and certain types of cancer, uptake is suboptimal. HPV vaccine requirements for school entry are an underutilized strategy to increase HPV vaccine uptake among adolescents. The purpose of this study was to understand the factors that are predictive of parents' attitudes toward schools requiring the HPV vaccine for entry into middle school. Parents of adolescents ages 11-12 y were recruited to participate in an online survey via Qualtrics. Descriptive frequencies were obtained, and sequential regression analyses were conducted controlling for demographic characteristics. A total of 1,046 participants were included in the analysis. The mean age was 40.3 y (SD = 6.3) and the majority of participants were White (74.4%) and had some college education or higher (80.9%). Participant's gender, political affiliation, urban/rural setting, and education level were significantly associated with attitudes toward school entry requirements. Adding psychosocial items related to perceptions of benefits, risks, and social norms significantly increased the amount of variance explained in the model [(ΔR2 = .312, F(5, 1036) = 132.621)]. Perceived social norms was the strongest predictor of attitudes [β = 0.321]. The results of this study can be used to inform policy changes around school-entry requirements in the United States. Further studies are needed to assess the influence of perceived social norms in vaccine hesitant groups.